2019
DOI: 10.1158/1055-9965.epi-18-0281
|View full text |Cite
|
Sign up to set email alerts
|

GALAD Score for Hepatocellular Carcinoma Detection in Comparison with Liver Ultrasound and Proposal of GALADUS Score

Abstract: Background: The GALAD score is a serum biomarkerbased model that predicts the probability of having hepatocellular carcinoma (HCC) in patients with chronic liver disease. We aimed to assess the performance of the GALAD score in comparison with liver ultrasound for detection of HCC.Methods: A single-center cohort of 111 HCC patients and 180 controls with cirrhosis or chronic hepatitis B and a multicenter cohort of 233 early HCC and 412 cirrhosis patients from the Early Detection Research Network (EDRN) phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
172
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(177 citation statements)
references
References 33 publications
1
172
0
4
Order By: Relevance
“…The lower performance in the USS-American cohort might be caused by smaller group sizes (30 NASH-HCC, 49 non-HCC NASH) in this etiology. Interestingly, Yang et al 11 identified the ideal GALAD cutoff to detect NASH-HCC at -0.86, which is between the established cutoff and the one identified by us.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The lower performance in the USS-American cohort might be caused by smaller group sizes (30 NASH-HCC, 49 non-HCC NASH) in this etiology. Interestingly, Yang et al 11 identified the ideal GALAD cutoff to detect NASH-HCC at -0.86, which is between the established cutoff and the one identified by us.…”
Section: Discussionmentioning
confidence: 54%
“…significantly superior to USS for HCC detection. However, Yang et al 11 found only an AUC of 0.89 for NASH-specific HCC detection by GALAD, which was not significantly better than USS. In the present multicenter study of NASH-HCC patients we demonstrate an excellent performance of the GALAD for detection of NASH HCC (AUC, 0.96).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of DCP for surveillance in conjunction with AFP and AFP‐L3 is common in practice and endorsed by clinical practice guidelines in China and Japan. All three tumor markers are incorporated in the GALAD (gender, age, AFP‐L3, AFP, and DCP) score, which has been validated extensively . DCP may perform better in the setting of advanced tumor stage with portal vein invasion.…”
mentioning
confidence: 99%